Pandemic beyond the metropolis: analysis of Covid-19 interiorization in the state of Ceara - Fernandes, Jefferson Santos [UNESP]; Silva, Jose Borzacchiello da; Vieira Muniz, Alexsandra Maria (Revues Org, 2021)
The new Coronavirus pandemic is a spatial phenomenon directly related to the flow of people in the territory and, therefore, large cities were the initial epicenter of the current health crisis. However, the circulation of the virus in small towns became an important focus of public managers attention due to the lack of hospital infrastructure. In this research, we analyzed the interiorization process of Covid-19 in Ceara. The accomplishment of the work took place from the literature review, statistical analysis and construction of thematic maps. The imbalance of the Ceara urban network and socio-spatial inequalities in access to health services constitute a barrier to actions to deal with the pandemic. Covid-19 exacerbated the need to strengthen local health and social protection networks for the most economically vulnerable population.
Keywords: Pandemic; urban network; health services; Ceara; small towns